Association of Thrombocytopenia and C-reactive Protein in COVID-19 Patients Attending a Tertiary Care Hospital - Kouser, Shaheen; Abbas, Farah Fatima; Khan, Nehad; Farooqui, Waqas Ahmed; Kamil, Saba; Khan, Ramsha (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: This study evaluates the frequency and relationship between Thrombocytopenia and CRP levels in Covid-19 patients. METHODOLOGY: The cross-sectional retrospective study was conducted at Dr. Ishrat ul Ebad Khan Institute of Blood Diseases from October 2021 to September 2022. Data was collected from existing data from the blood bank and hematology laboratory. C reactive protein (CRP) and complete blood count (CBC) levels were observed in Covid-19 patients. Both genders, all age groups, COVID-19 patients and patients having Thrombocytopenia and raised levels of CRP were included in this study. At the same time, other bone marrow transplant patients and other infectious diseases such as Hepatitis B, Hepatitis C, Dengue, and Malaria were excluded from this study. Statistical analysis was done by using the SPSS 20.0 version. RESULTS: Out of 844 patients, the mean age was 50 years, and the male proportion was high at 70% (n=590). Most patients, 95% (n=803) had grade 1 thrombocytopenia. The mean age was found to be higher (>50 years) in Grades 1 and 2 as compared to Grades 3 and 4, where we found (<40 years). A significant (p=0.002) mean age difference among grades was found. No significant (p=0.749) median difference in CRP among Grades were found. CONCLUSION: The current study shows that COVID-19 significantly increases C-reactive protein levels. While treating and managing the patients of COVID-19, it is essential to detect the biomarkers that can predict the severity and prognosis of this disease.